Analisis Preferensi Calon Mahasiswa Terhadap Program Studi dengan Menggunakan Cochran Q Test dan Analytical Hierarchy Process (AHP) - Susanta, Susanta (Jurnal Ilmu Administrasi dan Bisnis, 2010)
We use decision making theory to know hierarchy structure of consumer decision. By using Cochran Qtest and analytical hierarchy process (AHP), we analyse 68 students candidate which are searching department Three factors becoming especial consideration of student in choosing department are cost factor with sub factor expense of study, according to aspiration frictor with sub factor according to aspiration, easiness factor of selection with sub factor availability of department information, Keyword; Student Preference, Cochran Qtest, Analytical hierarchy process (AHP).Â